Cadaver Donation and Bequeathment in Medical Education - Farnaz Limouei; Hossein Limouei; Omid Ali Hoseinzadeh; Bahram Asl-Fattahi; Parviz Karimi-Sani; Kavous Shahsavarinia (Kerman University of Medical Sciences, 2016)
Background & Objective: Anatomy is the basis of medical education and is conducted by the dissection of the cadaver The cadaver is a book which can provide great educational grounds for medical and paramedical students However cadaver shortage is one of the most important problems of medical schools in Iran; a subject that despite high levels of theoretical training of the anatomy has created problems for the practical training of this science Methods: In this study scientific references articles and reports have been analyzed to determine the role of cadaver donation and its obstacles and the effect of bequeathment in the elimination of these obstacles Results: Findings have shown that experiences gained through dissecting cadaver are better and more effective than knowledge obtained from books or models For more effective education cadavers are constantly required Cadaver shortage has been the topic of discussions and complaints of anatomy professors and medical students for consecutive years Providing cadavers or dissection is a complicated subject which requires cultural training The provision of unidentified cadavers by morgues can result in both remuneration for the deceased and steps towards the acquiring of knowledge Conclusion: The field of anatomy can only survive through cadaver donation Cadaver donation is an actual and effective way to support medical development and facilitate life of future generations Legal religious and cultural obstacles impede cadaver bequest The elimination of these obstacles is possible through the establishment of cadaver donation institutes cultural promotion and creation of motive and awareness in the society